Fabrication of ZrO2 and ATZ materials via UV-LCM-DLP additive manufacturing technology. Issue 4 (April 2020) - Borlaf, Mario; Szubra, Natalia; Serra-Capdevila, Albert; Kubiak, Wladyslaw W.; Graule, Thomas
Abstract: The development of photosensitive slurries for additive manufacturing is attracting high interest due to their correlation with the final properties of the fabricated parts. Lithography-based ceramics manufacturing (LCM), i.e. digital light processing (DLP), is one of the techniques that is receiving high attention. Within the different ceramic materials, ZrO2 and ATZ are the most studied due to their potential applications including in the dental field. In this work, the fabrication of ZrO2 and ATZ materials via LCM-DLP is shown. A comparison between one- and two-step procedures to develop UV-curable ZrO2 and Al2 O3 -ZrO2 slurries was performed. The printed parts with a relative density of ∼99% for both ZrO2 and ATZ were subjected to 4-point bending measurements, obtaining flexural strength values around 800 MPa for both ZrO2 and ATZ materials prepared by using the one-step slurry.